Effects of Virtual Reality (VR) Video as Asynchronous e-Learning Supplement on Student Learning Outcomes - Ismail, Ismail (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The purpose of this study is to explore the impact of virtual reality (VR) videos as asynchronous e-learning supplements on improving student learning outcomes. This study is an experimental study, using two sample groups (experimental and control). The experimental group was taught by presenting virtual reality (VR) videos connected to e-learning in the LMS, and the control group by traditional (face-to-face) or expository learning (without VR). Research participants in each sample group were 24 early semester students who programmed a basic natural science course at the Universitas Pendidikan Mandalika (UNDIKMA). The groups were given the initial task as a pretest, learning treatment, and the final task as a posttest. Learning assignments and descriptions of learning materials are related to the theme of ’climate change.’ Test instruments (essays) were employed to measure students’ cognitive learning outcomes. The test instrument used fulfills the validity aspect as a psychometric property of the instrument. Data were analyzed descriptively (n-gain parameter), and statistically (analysis of mean differences using independent sample t-test) at a significance level of 0.05. The results of the descriptive and statistical tests showed that there was a significant impact from the application of virtual reality (VR) videos as asynchronous e-learning supplements to the improvement of student learning outcomes. Our findings confirm that virtual reality (VR) videos as asynchronous e-learning supplements are better at improving student learning outcomes when compared to traditional face-to-face (expository) learning. More detailed results are presented in this article.